1992
DOI: 10.1029/92ja00303
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of low‐β plasma clouds as simulated by a three‐dimensional, electromagnetic particle code

Abstract: The dynamics of low‐β plasma clouds moving perpendicular to an ambient magnetic field in vacuum and in a background plasma is simulated by means of a three‐dimensional, electromagnetic, and relativistic particle simulation code. The simulations show the formation of the space charge sheaths at the sides of the cloud with the associated polarization electric field which facilitate the cross‐field propagation, as well as the sheaths at the front and rear end of the cloud caused by the larger ion Larmor radius, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Galvez et al, 1988;Livesey and Pritchett, 1989;Galvez and Borovsky, 1991;Cai and Buneman, 1992) particle-in-cell codes, but also electromagnetic threedimensional PIC simulations (e.g. Neubert et al, 1992). The computer experiments performed emphasized the self-polarization of plasma elements and their propagation across the transverse magnetic field, as described by Schmidt's model (Schmidt, 1960).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galvez et al, 1988;Livesey and Pritchett, 1989;Galvez and Borovsky, 1991;Cai and Buneman, 1992) particle-in-cell codes, but also electromagnetic threedimensional PIC simulations (e.g. Neubert et al, 1992). The computer experiments performed emphasized the self-polarization of plasma elements and their propagation across the transverse magnetic field, as described by Schmidt's model (Schmidt, 1960).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Table 2 compares the input parameters of particle-in-cell simulations performed to study the plasma motion across transverse magnetic fields and published in the literature in the last two decades: the two-dimensional electrostatic simulations of Livesey and Pritchett (1989) and Galvez and Borovsky (1991), the three-dimensional electromagnetic simulations of Neubert et al (1992) and the three-dimensional electrostatic simulations by Gunell et al Cluster and THEMIS spacecraft (Karlsson et al, 2012;Plaschke et al, 2013). The numerical simulations of Livesey and Pritchett (1989), Galvez and Borovsky (1991) and Neubert et al (1992) have been performed for a uniform magnetic field, while the geometry used in the study of Gunell et al (2009) is closely related to laboratory experiments with large Larmor radius plasma clouds entering a curved magnetic field (see also Hurtig et al, 2003). To our knowledge, the present study shows the first three-dimensional particle-in-cell simulations of a small Larmor radius plasma cloud transported across a non-uniform magnetic profile typical to a tangential discontinuity (as the magnetopause).…”
mentioning
confidence: 99%
“…The energy of accelerated particles is ¥ ZeU where Ze is the particle charge and U is one-half of the electrostatic potential difference across the plasma stream. This phenomenon of particle acceleration and the above estimate of particle energy has been verified in experiments (Lindberg 1978) and in computer simulations (Galvez & Borovsky 1991, Neubert et al 1992.…”
Section: Acceleration Mechanismmentioning
confidence: 79%
“…This phenomenon has been observed in numerical simulations [14][15][16] which showed that charge layers can accelerate particles to relativistic energies even for relatively slow (sub-Alfvénic) plasma flows; the accelerated particle energy E is ∼ qΦ 0 , where q is the particle charge. This estimate for E derives from the fact that the electrostatic field is dipole-like outside the plasma, giving rise to the potential drop on the order of Φ 0 along B [15].The process of particle acceleration is transient: The energetic particle outflow from boundary layers of the plasmoid gives rise to plasma current; the resulting force decelerates the plasmoid cross-field motion (see below).As an example, consider a plasmoid with h ∼ 10 km infalling at the the free-fall velocity onto the surface of a canonical neutron star of mass M * = 1.4M , radius R * = 10 km and surface magnetic field B * = 5 × 10 …”
mentioning
confidence: 91%
“…This phenomenon has been observed in numerical simulations [14][15][16] which showed that charge layers can accelerate particles to relativistic energies even for relatively slow (sub-Alfvénic) plasma flows; the accelerated particle energy E is ∼ qΦ 0 , where q is the particle charge. This estimate for E derives from the fact that the electrostatic field is dipole-like outside the plasma, giving rise to the potential drop on the order of Φ 0 along B [15].…”
mentioning
confidence: 91%